Radiofrequency Ablation of Parathyroid Glands to Treat a Patient With Hypercalcemia Caused by a Novel Inactivating Mutation in CaSR - Hao, Yu; Lei, Zhikai; Shi, Nanjing; Yu, Lingying; Ji, Weiqin; Zhang, Xianfeng (Frontiers in Endocrinology, 2022)
Objective: We identified a novel inactivating mutation in the calcium-sensing receptor (CaSR) gene in a patient with refractory hypocalciuric hypercalcemia and analyzed its function. The effectiveness of radiofrequency ablation of the parathyroid glands to treat hypercalcemia caused by this mutation was explored. Methods: Clinical data of the patient before and after radiofrequency ablation was retrospectively analyzed. The CaSR mutation (D99N) found in the patient was studied in cell lines. HEK-293 cells were transfected with plasmids containing wild-type (WT) or mutant CaSR genes (D99N and W718X). Expression levels of the respective CaSR proteins were measured, and their functions were assessed by examining the effect of NPS-R568 (a CaSR agonist) on intracellular Ca2+ oscillations and that of exogenous parathyroid hormone (PTH) on intracellular cAMP levels. Results: The effectiveness of pharmacological treatment was poor, whereas radiofrequency ablation of the parathyroid glands resulted in controlled blood calcium and PTH levels in the patient. In cell lines, upon NPS-R568 administration, the amplitude of intracellular Ca2+ oscillations in the D99N group was lower than that in the WT group and higher than that in the W718X group. Upon administration of PTH, intracellular cAMP levels in the D99N group were higher than those in the WT group and lower than those in the W718X group. Conclusion: The homozygous mutation D99N reduced CaSR activity and caused more severe hypocalciuric hypercalcemia. For patients with this type of hypercalcemia and poor response to pharmacological treatments, radiofrequency ablation of the parathyroid glands may be a suitable treatment option.